Ultra‐Broad Emission Copper Halide Scintillator‐Based X‐Ray Imager - Haocheng Lv; Wenyi Shao; Haifeng Chen; Guoyang Zhu; Yao Wang; Zhenzhong Zhang; Hongwei Liang (Advanced Science)
Abstract Lead‐free metal‐halide scintillators are gaining considerable attention as more eco‐friendly and superior alternatives to their lead‐based counterparts. However, novel broad‐emission band scintillators like the state‐of‐the‐art CsI: Tl scintillator, which can generate high signals due to its strong compatibility with the spectral responsivity of regular photodiode arrays, are still less investigated. Herein, a TPA2Cu2I4 (TPACI) copper halide scintillator with a unique ultra‐broad emission (FWHM > 240 nm) is developed, which shows universal compatibility with the peak response range of commercial photodetector. The optical properties characterization and mechanism analysis indicates that this ultra‐broad spectrum can be attributed to the dual self‐trapped exciton (STE) emission consisting of two emission bands. Benefiting from the large Stokes shift and ultra‐broad emission band enabled by the dual STE, the self‐absorption‐free TPACI scintillator exhibits efficient white light emission with a high photoluminescence quantum yields of 94.27%, a high light yield of ≈40124 photons MeV−1. Moreover, a prototype of a TPACI scintillator‐based X‐ray imager is assembled for inspecting the internal structures of biological and electronic devices, which demonstrated a high resolution of 5.5 lp mm−1 at modulation transfer function = 0.2. These findings provide insights into the design of efficient, broad‐emission scintillators for high‐resolution X‐ray imaging.